Digital credit and the gender gap in financial inclusion: Empirical evidence from Kenya - Constantin Johnen; Oliver Mußhoff (Journal of International Development, 2022)
Formal digital credit raises hopes to decrease the gender gap in financial inclusion. However, up until now, it remains unknown whether these hopes are justified. Using nationally representative household surveys from Kenya, the present study aims to fill this gap. We find strong indication that formal digital credit, contrasting to expectations, has led to an increase in the gender gap in financial inclusion. We further find indication that the pervasive gender gap in the formal digital credit market is largely attributable to gender differences in socio-economic variables in combination with a lack of contract term heterogeneity in that market. The paper suggests that policies to strengthen women's position in society and/or to encourage contract term heterogeneity in the formal digital credit market could decrease the gender gap in financial inclusion.
Keywords: 300; digital financial services; formal credit; gender equality; regulation